Sheep Acclimation in the Andean highlands - Monge M., Carlos (1945)
The aggressive action of the physical and chemical causes on male gonads has received increased attention in recent years. Thus in the excellent magazine Hueper, which we refer to knowledge of the literature until 1942, it realizes the exogenous factors that may act on the germinal epithelium causing loss of libido, azoospermia and tissue damage, reversible sometimes and other irreversible.